Algal biotechnology and the beneficiation of saline effluent wastes - Rose, Peter Dale (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1992)
Saline deterioration in the South African public water system has been documented and disposal of brine wastes has been identified as part of the problem. The broad aim of this research programme was to undertake an initial technical study to evaluate the feasibility of integrating algal biotechnology into a disposal function for these wastes. A demonstration of utility in the form of products and waste treatment could produce a beneficiation of saline effluents and provide incentives necessary to deal with the disposal issue. The study attempted to demonstrate a synthesis between the two main thrusts in algal biotechnology that have produced large-scale practical applications - stable, predictable algal production in saline media and the cost effective High Rate Oxidation Ponding (HROP) process for incorporating algal production into a waste treatment function. Tannery organic saline effluents and the biotechnology of Dunaliella salina culture producing Î²- carotene were chosen as paradigms for the study. 1. The alga was shown to grow in certain tannery effluents producing enhanced biomass yields compared to defined inorganic medium cultivation. The potential for amino acid or protein supplementation of defmed culture media was noted. 2. A reduction in organic load simultaneous with the growth of D.salina was recorded in laboratory-scale simulations of the HROP process. Rates similar to the fresh water HROP equivalent were demonstrated. 3. These results suggested the uptake and storage of organic nitrogen by D.salina. The consequent inhibition of Î²-carotene accumulation by the organism presented a potentially insurmountable obstacle to the feasibility of Î²-carotene production in this medium. Uptake and release of organic compounds, previously demonstrated in phytoplankton and other micro-algae, was confirmed in this study for D.salina. The evidence acquired indicated the internalization of both glycine and bovine serum albumin. An ultrastructural study demonstrated mechanisms by which this process might occur. 4. The release of substantial quantities of glycerol was shown. A mechanism whereby D. salina may use this to regulate ammonia availability via control of its associated bacterial population was observed. Glycerol release was identified as presenting an application in treating refractory organic wastes, such as secondary sewage sludges, by elevating C:N ratios. This could demonstrate a significant utility for brine waste impoundments. 5. A multistage production process was proposed to deal with the problem of Î²-carotene inhibition by separation of the growth and metabolite accumulation functions into separate unit operations. It was shown in this study that the stress of nitrogen deficiency combined with high salinity provides for effectiveÎ²-carotene accumulation under the conditions of low illumination that pertain in dense cultures. Subjected to these conditions effluent-grown cells show delayed but unimpaired {j-carotene accumulation. 6. A role for the plant hormone abscisic acid in mediating the stress response was demonstrated in D.salina. Fluorescence induction studies suggested the presence of a signalling process forming part of a sensitivity control mechanism. Stress induction of Î²-carotene accumulation could occur through four clearly defined stages. Potential was identified for using this response as a physiological probe for monitoring and regulating the stress induction process. 7. The multistage processing concept requires effective algal cell separation technology. The use of cross-flow ultrafiltration and diafiltration with a polyethersulfone tubular membrane system was demonstrated as an effective process for the recovery and washing of D. salina. Cell concentrates were produced in a viable form. 8. Process designs incorporating the findings of the research programme are presented demonstrating how effluent and organic waste treatment functions may be combined with the production of D.salina and its products. Application of the multi-stage processing concept to Î²-carotene production in a defined medium process was identified as offering a potential four-fold yield enhancement. This could have a significant impact on a high cost, marginal algal biotechnology process. Aspects of novelty have been claimed in provisional patents applications. A provisional demonstration of the feasibility of D.salina production in tannery effluent indicates that algal biotechnology may provide a utility for, and hence the beneficiation of saline effluent wastes.
Keywords: Algae -- Biotechnology; Algae culture; Tanneries -- Waste disposal